Longitudinal healthcare use after pediatric brain injury: A population-based birth cohort study. - Vincy Chan; Clarissa Serafine Wirianto; Robert Balogh; Michael David Escobar (PLoS ONE)
Background Traumatic brain injury is a chronic disease with lifelong consequences. In children, it can affect developmental milestones. Longitudinal data on brain injury and long-term healthcare use is limited, with lack of clarity on social determinants of health and its effects on healthcare use. This study explores rates of healthcare use, from birth, and up to 10 years after a childhood traumatic brain injury-related healthcare visit. Methods and findings This study uses a population-based birth cohort of individuals born between April 1, 2002 and March 31, 2020 from Ontario, Canada. A case cohort (TBI cohort) was created using a sample of individuals who had at least one traumatic brain injury-related healthcare visit between the ages of 0 and 4 years, inclusive (n = 26,988). Controls were generated from a sample of individuals who did not have any traumatic brain injury-related healthcare visit during the study period (n = 193,253 for emergency department visits and hospitalizations, and n = 19,313 for primary care physician visits). The primary outcome is rates of primary care physician visits, emergency department visits, and hospitalizations for each year prior to and up to 10 years after the index traumatic brain injury-related healthcare visit, calculated using standard life table methods. Rates and 95% confidence intervals were further calculated and stratified by rurality of residence, and the following Ontario Marginalization Index metrics: neighbourhood income quintile and neighbourhood racialized and newcomer populations. Rates of healthcare use remained consistently higher in the TBI cohort compared to controls both prior to and after the index TBI-related healthcare visit. Rates also varied across social determinants of health. Overall, rates were higher in males compared to females across all healthcare settings. Rates of primary care physician visits were higher among those living in urban (vs. rural) settings. However, rates of emergency department visits were higher among those living in rural (vs. urban) settings. Rates of emergency department visits and hospitalizations were higher among those living in the lowest (vs. highest) income quintile neighbourhoods. Rates of primary care physician visits were higher among those living in areas with the most (vs. least) racialized and newcomer populations. However, rates of emergency department and hospitalizations were higher among those living in areas with the least (vs. most) racialized and newcomer populations. This study is limited to change in rates of healthcare use over time and does not quantify the magnitude of these changes. Conclusions Research on longitudinal healthcare use is needed to explore the causes of sustained and increased healthcare use post-injury, to inform opportunities for targeted health and social care interventions. Findings also suggest that a lifespan perspective is critical to understand how early life events can impact post-injury outcome.